Dopamine Functioning and Child Externalizing Behavior: A Longitudinal Analysis of Polygenic Susceptibility to Parenting. Issue 8 (October 2020) - Fischer, Karen; van den Akker, Alithe L.; Larsen, Helle; Jorgensen, Terrence D.; Overbeek, Geertjan
ABSTRACT: Objective: This study investigated how genetic susceptibility may affect children's sensitivity to parenting practices in their development of externalizing behavior. We created a continuous polygenic index composed of 5 dopamine polymorphisms to investigate the moderating role of dopamine-related genes in shaping parent-child gene-by-environment (Gc×E) interactions. Accumulating research supports that differences in children's dopamine neurotransmission make certain children more susceptible to both negative and positive parenting practices, a "for-better and for-worse" effect. Methods: Data from a 3-wave longitudinal study (4 months between waves) on 190 at-risk families with children aged 4 to 8 were used to investigate whether a heightened polygenic index score amplified the associations between negative and positive parenting and later children's externalizing behavior. Parenting practices and child externalizing behavior were assessed by parent-reported questionnaires. Results: Findings were not in line with the expectation that there was a stronger association between positive and negative parenting and later externalizing behavior for children with higher scores on the polygenic susceptibility index. Rather, children with a lower score on the polygenic susceptibility index showed more later externalizing behavior in response to positive parenting behavior, whereas for children with a higher score on the polygenic index, positive parenting was predictive of relatively lower levels of later child externalizing behavior. Conclusion: The results indicate that not only are children with higher but also lower scores on the polygenic index sensitive to parenting, they suggest that different phenotypical characteristics related to reward processing might underlie these genetic susceptibilities to parenting practices. Abstract : This article has supplementary material on the web site: www.jdbp.org.